2019
DOI: 10.1097/dcr.0000000000001301
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Postoperative Ileus Significantly Increases the Cost of Inpatient Stay for Patients Undergoing Elective Colorectal Surgery: Results of a Multivariate Analysis of Prospective Data at a Single Institution

Abstract: BACKGROUND: Prolonged postoperative ileus is a common major complication after abdominal surgery. Retrospective data suggest that ileus doubles the cost of inpatient stay. However, current economic impact data are based on retrospective studies that rely on clinical coding to diagnose ileus. OBJECTIVE: The aim of this study was to determine the economic burden of ileus for patients undergoing elective colorectal surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 29 publications
7
65
6
Order By: Relevance
“…There have been numerous reports on PPOI after colectomy with prediction or post hoc analyses . However, little is known about risk factors of PPOI for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been numerous reports on PPOI after colectomy with prediction or post hoc analyses . However, little is known about risk factors of PPOI for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A global survey and systematic review extracted definitions from 52 identified trials and proposed 4 days as a standardized endpoint for PPOI . It was well accepted in subsequent studies, and we also adopted this definition as diagnostic criteria in our study . Given the variability in the definitions of this significant complication, further research is necessary to establish a more precise, validated definition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations